Discovery of peptides for ligand-mediated delivery of mRNA lipid nanoparticles to cystic fibrosis lung epithelia - Melissa R. Soto; Mae M. Lewis; Jasmim Leal; Yuting Pan; Rashmi P. Mohanty; Arian Veyssi; Esther Y. Maier; Brittany J. Heiser; Debadyuti Ghosh (Elsevier, 2024)
For cystic fibrosis patients, a lung-targeted gene therapy would significantly alleviate pulmonary complications associated with morbidity and mortality. However, mucus in the airways and cell entry pose huge delivery barriers for local gene therapy. Here, we used phage display technology to select for and identify mucus- and cell-penetrating peptides against primary human bronchial epithelial cells from cystic fibrosis patients cultured at the air-liquid interface. At the air-liquid interface, primary human bronchial epithelial cells produce mucus and reflect cystic fibrosis disease pathology, making it a clinically relevant model. Using this model, we discovered a lead candidate peptide and incorporated it into lipid nanoparticles to deliver mRNA to primary human bronchial epithelia in vitro and mouse lungs in vivo. Compared to lipid nanoparticles without our peptide, peptide-lipid nanoparticles demonstrated up to 7.8-fold and 3.4-fold higher reporter luciferase bioactivity in vitro and in vivo, respectively. Importantly, these peptides facilitated higher specific uptake of nanoparticles into lung epithelia relative to other cell types. Since gene delivery to primary human bronchial epithelia is a significant challenge, we are encouraged by these results and anticipate that our peptide could be used to successfully deliver cystic fibrosis gene therapies in future work.